(untitled) (Journal of Science and Technology, 2016)
The study uses cross sectional data from randomly selected oil palm famers to describe the struc- ture of the labour market and estimate the factors which influence oil palm farmers’ demand for hired labour in the Western Region. Descriptive statistics and the ordinary least square regres- sion techniques have been applied in the analysis. The results suggest that the structure of la- bour for oil palm production typifies a small-scale agricultural production, with some farmers using contract labour (14 percent), salaried labour (11 percent) and fertilizer (30 percent) in production. The estimated regression results show that the value of investment in other inputs (e.g. fertilizer), village wage rate, size of oil palm farm and higher educational attainment have significant and positive influences on oil palm farmers’ demand for hired labour. The distance of the farm from home has a negative and significant influence. The estimated hired labour de- mand elasticities for farm size, value of other inputs, village wage rate and distance are inelastic. It is noted that issues on labour requirement of farmers should be based on economic considera- tions such as the structure of labour of the farmers, farm size, village wage rate and cost of other productive inputs. For oil palm production, carrying of fresh fruit bunches and slashing are two main activities that could be mechanized, but may lead to retrenchment of female and male hired labour, respectively.